Synthesis of Piperine-Based Ester Derivatives with Diverse Aromatic Rings and Their Agricultural Bioactivities against Tetranychus cinnabarinus Boisduval, Aphis citricola Van der Goot, and Eriosoma lanigerum Hausmann - Tianze Li; Min Lv; Houpeng Wen; Yanyan Wang; Sunita Thapa; Shaoyong Zhang; Hui Xu (Insects, 2022)
Exploration of plant secondary metabolites or by using them as leads for development of new pesticides has become one of the focal research topics nowadays. Herein, a series of new ester derivatives of piperine were prepared via the Vilsmeier–Haack–Arnold (VHA) reaction, and their structures were characterized by infrared spectroscopy (IR), melting point (mp), proton nuclear magnetic resonance spectroscopy (1H NMR), and carbon nuclear magnetic resonance spectroscopy (13C NMR). Notably, the steric configurations of compounds 6 and 7 were confirmed by single-crystal analysis. Against T. cinnabarinus, compounds 9 and 11 exhibited 47.6- and 45.4-fold more pronounced acaricidal activity than piperine. In particular, compounds 9 and 11 also showed 2.6-fold control efficiency on the fifth day of piperine. In addition, compound 6 (>10–fold higher than piperine) displayed the most potent aphicidal activity against A. citricola. Furthermore, some derivatives showed good aphicidal activities against E. lanigerum. Moreover, the effects of compounds on the cuticles of T. cinnabarinus were investigated by the scanning electron microscope (SEM) imaging method. This study will pave the way for future high value added application of piperine and its derivatives as botanical pesticides.